Advances in diagnosis and treatment of trigeminal neuralgia - Montano N; Conforti G; Di Bonaventura R; Meglio M; Fernandez E; Papacci F (Dove Medical Press, 2015)
Nicola Montano,1 Giulio Conforti,1 Rina Di Bonaventura,1 Mario Meglio,2 Eduardo Fernandez,1 Fabio Papacci1 1Institute of Neurosurgery, Catholic University, Rome, 2Institute of Neurosurgery, Azienda Ospedaliera Universitaria Integrata, Verona, Italy Abstract: Various drugs and surgical procedures have been utilized for the treatment of trigeminal neuralgia (TN). Despite numerous available approaches, the results are not completely satisfying. The need for more contemporaneous drugs to control the pain attacks is a common experience. Moreover, a number of patients become drug resistant, needing a surgical procedure to treat the neuralgia. Nonetheless, pain recurrence after one or more surgical operations is also frequently seen. These facts reflect the lack of the precise understanding of the TN pathogenesis. Classically, it has been related to a neurovascular compression at the trigeminal nerve root entry-zone in the prepontine cistern. However, it has been evidenced that in the pain onset and recurrence, various neurophysiological mechanisms other than the neurovascular conflict are involved. Recently, the introduction of new magnetic resonance techniques, such as voxel-based morphometry, diffusion tensor imaging, three-dimensional time-of-flight magnetic resonance angiography, and fluid attenuated inversion recovery sequences, has provided new insight about the TN pathogenesis. Some of these new sequences have also been used to better preoperatively evidence the neurovascular conflict in the surgical planning of microvascular decompression. Moreover, the endoscopy (during microvascular decompression) and the intraoperative computed tomography with integrated neuronavigation (during percutaneous procedures) have been recently introduced in the challenging cases. In the last few years, efforts have been made in order to better define the optimal target when performing the gamma knife radiosurgery. Moreover, some authors have also evidenced that neurostimulation might represent an opportunity in TN refractory to other surgical treatments. The aim of this work was to review the recent literature about the pathogenesis, diagnosis, and medical and surgical treatments, and discuss the significant advances in all these fields. Keywords: microvascular decompression, percutaneous balloon compression, gamma knife radiosurgery, surgical treatment, magnetic resonance imaging, therapy